Altered Phospholipid Metabolism in Escherichia coli Accompanying Killing by Disrupted Granulocytes - Mooney, Carolyn (1975)
The effect of bactericidal concentrations of disrupted rabbit granulocytes and of partially purified granulocyte fractions on phospholipid metabolism by Escherichia coli has been investigated. Previous studies in this laboratory have shown that, during and after killing of E. coli by granulocytes, bacterial macromolecular synthesis continues. Similarly, despite almost complete loss of viability within 15 min, incorporation of [1-(14)C]palmitate, [2-(14)C]glycerol, and [1-(14)C]acetate into E. coli phospholipids, in the presence of granulocyte preparations, remains the same as in control E. coli populations for at least 1 h. Incorporation of [1-(14)C]oleate into E. coli phospholipids is actually stimulated during the first 60 min of incubation in the presence of granulocyte preparations (more than twofold at 30 min and 40% at 60 min). With all labeled lipid precursors, bactericidal granulocyte preparations cause a relative increase in the labeling of E. coli cardiolipin, with a corresponding drop in labeled phosphatidyl-glycerol. Labeled lyso-compounds accumulate in the presence of granulocyte preparations when [1-(14)C]palmitate, but not when [1-(14)C]oleate is the labeled precursor. Since oleate occurs mainly in the 2-acyl position of E. coli phospholipids, whereas at least 50% of palmitate occurs in the 1 position, it appears that a phospholipase A(2) acts on the E. coli phospholipids. These various effects are also seen when E. coli are exposed to highly purified granulocyte preparations that possess potent bactericidal and phospholipase A(2) activities. We speculate that this phospholipase A(2) in the granulocyte preparations stimulates oleate but not palmitate incorporation by initiating increased turnover of the fatty acid in the 2-acyl position of E. coli phospholipids, causing formation of 1-acyl lyso-compounds likely to be preferentially reacylated with unsaturated fatty acids.